Обґрунтування діаметра обсадної труби ґрунтового теплообмінника та подачі повітря в нього - Ковязін, Олексій Сергійович (НТУ "ХПІ", 2018)
Використано попередньо розроблену математичну модель процесу теплообміну між повітрям, що рухається в вертикальному теплообміннику і масивом ґрунту, яка пов'язує між собою енергетичні показники ґрунтового теплообмінника із його параметрами, а також природно-кліматичними умовами. На основі максимізації введеного критерію оптимізації, який назвали енергоозброєністю ґрунтового теплообмінника, обґрунтовано діаметр обсадної труби ґрунтового теплообмінника та об'ємну подачу повітря в нього.

The purpose of the research done was to increase the efficiency of geothermal ventilation that allows us to use the thermal energy of surface layers of the earth for the cooling and heating of the inflow air by substantiating the diameter of the liner pipe of the earth heat exchanger with the volumetric air supply to it. Mathematical simulation was done based on the equations of hydrodynamics, heat exchange and heat conductivity carrying out the computation experiment based on the method of finite volumes. A preliminary developed mathematical model of the heat exchange process between the air moving in the vertical heat exchanger and the soil in-situ was used. This model interconnects the energy indicators of the earth heat exchanger with its parameters including natural climatic conditions. Temperature fields of the cooled air and the soil in-situ were determined and as a consequence, the effective heat power of the earth heat exchanger, the volumetric supply and the ambient air temperature and heat exchanger operation time were also determined for different diameters of the liner pipe. An efficient heat power of the earth heat exchanger is gradually decreased with time. An abrupt drop in power corresponds to an ample air supply to the heat exchanger and it can be explained by a faster exhaustion of the power potential of soil and high energy inputs for the pumping of air through it. An optimization criterion was the relation of the effective thermal energy produced during the earth heat exchanger operation to the diameter of its liner pipe that was named as the power loading of the earth heat exchanger. Based on the maximization of optimization criterion we substantiated the diameter of liner pipe and that of the earth heat exchanger and the volumetric air supply to it.
Substantiating the diameter of the liner pipe of the earth heat exchanger and providing the air supply to it
Keywords: поверхневі шари Землі; теплова енергія; енергоозброєність; коефіцієнт корисного використання; енергетичний потенціал ґрунту; surface layers of the earth; thermal energy; earth heat exchanger; power loading; liner pipe diameter; air supply